2017
DOI: 10.1038/s41598-017-05970-1
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb plasticity ensures proper olfaction after severe impairment in postnatal neurogenesis

Abstract: The olfactory bulb (OB) neurons establish a complex network that ensures the correct processing of the olfactory inputs. Moreover, the OB presents a lifelong addition of new neurons into its existing circuitry. This neurogenesis is considered essential for the OB function. However, its functional impact on physiology and behavior is still unclear. Here, we investigate the mechanisms of OB plasticity that underlie bulbar physiology in relation to severe damage of neurogenesis. The neurogenesis of young mice was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…In the attempts to determine the molecular phenotype of BrdU labeled cells around the distinct glomerulus types, double staining experiments for BrdU and the neuronal marker NeuN were performed. A generally low number of adult born periglomerular cell types in the glomerular area was also reported in a previous study (Díaz et al, 2017 ). Therefore, the numbers of double labeled cells are given in absolute numbers, as well as the total numbers of marker labeled populations towards a direct comparison.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the attempts to determine the molecular phenotype of BrdU labeled cells around the distinct glomerulus types, double staining experiments for BrdU and the neuronal marker NeuN were performed. A generally low number of adult born periglomerular cell types in the glomerular area was also reported in a previous study (Díaz et al, 2017 ). Therefore, the numbers of double labeled cells are given in absolute numbers, as well as the total numbers of marker labeled populations towards a direct comparison.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, 23 days after BrdU injection, less BrdU positive cells were found in the surrounding of OR37 glomeruli compared to glomeruli of other receptor types. The generally low numbers of adult born cells in the periglomerular region of individual glomeruli can be explained by the fact that only a small portion of adult born interneurons reach the Glomerular Layer (Hack et al, 2005 ; Alonso et al, 2008 ; García-González et al, 2016 ; Díaz et al, 2017 ), so that, under unstimulated conditions, only few cells can be observed in the direct surrounding of a single glomerulus (Khodosevich et al, 2013 ). In view of the fact that mice were injected with BrdU at four consecutive days three times a day, the data indicate a lower number of newly generated periglomerular cells which were born up to 27 days before analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even considering both hypotheses, we can assume that SCGN is involved in the processing of olfactory information by modulating the interneurons action (this will be discussed later on together with the activity analysis of c-Fos). In any case, both hypotheses support strong compensatory characteristics of the OB functionality, as it happens when other alterations occur in this structure, not only in rodents 39 but also in humans 40 .…”
Section: Discussionmentioning
confidence: 58%
“…Blocking neurogenesis by infusion of mitotic inhibitor cytosine arabinoside (AraC) in the SVZ before or during perceptual learning (i.e., odorant exposure) prevents the increase in inhibitory activity, thereby abolishing learning-acquired ability to distinguish chemically similar odorants (Moreno et al, 2009). While adult-born GCs improve learning-associated discrimination ability, spontaneous odor discrimination remains unaffected by ablation of neural stem cells in the adult SVZ by focal irradiation (Lazarini et al, 2009; Díaz et al, 2017) or AraC infusion (Breton-Provencher et al, 2009). Although the definite role of newborn GCs in fine-tuning which aspect of olfactory function remains active investigation, the results from CPEB4-KO mice indicate the indispensable role of neonate-born GCs in spontaneous odor discrimination.…”
Section: Discussionmentioning
confidence: 99%